PRELIMINARY STUDIES OF ANALYZING MISCONCEPTION AND SCIENTIFIC ARGUMENTATION USING DIAGNOSTIC QUESTION CLUSTERS (DQCS) OF MOLECULAR GENETICS CONCEPT - Lela Nurlaila; Siti Sriyati; Riandi Riandi (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2018)
This study aimed to analyze the misconceptions and argumentation ability Biology educationstudents using diagnostic question clusters on the concept of molecular genetics. In addition,this study aims to look at the pattern of misconceptions tendencies and scientificargumentation ability of students accompanied by the factors supporting the occurrence ofmisconceptions and arguments student achievement levels. As this study focused on theconcept of molecular genetics which includes the concept of genes, chromosomes, DNA, andprotein synthesis. This research was conducted with the descriptive research method and thesample using purposive sampling techniques. The subjects were biology education students ofIslamic University of Sunan Gunung Djati Bandung who attended the lectures of genetics inthe academic year 2014/2015. The instrument used is a matter of diagnostic question clusters(DQCs) which covers a combined essay and multiple choice questions, learning observationsheet, and interview guidelines used to determine the factors that cause the occurrence ofmisconceptions and what degree of scientific argumentation ability students. The ability of thescientific arguments that will be analyzed is the ability to claim, warrant, backing, andrebutal (Toulmin, 1984).